Hubungan Intertekstualitas Syair Paras Nabi Dan Hikayat Nabi Bercukur - Moh Muzakka (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The existence of a text cannot be separated from the previous texts. Because, the presence of a new text is greatly influenced by previous texts. This condition is called an intertextual relationship. The presence of the text of the Prophet's shaved story on Java must have been strongly influenced by other texts that had existed in Nusantara, and could even be influenced by Arabic texts. Because, the text of the Prophet's shave story is related to the history of the Prophet who was born and lived in Arabia. This study aims to look at the intertextual relationship of the Syair Paras Nabi from the Javanese text with Hikayat Nabi Bercukur from the Malay text. To achieve this goal, this study uses a comparative approach and an intertextual approach. The results showed that the comparison of textual data to the Syair Paras Nabi text and Hikayat Nabi Bercukur text in depth found that the Syair Paras Nabi text was a transformation text of the Hikayar Nabi Bercukur text that was seen as the hypogram text.